2017
DOI: 10.1007/s00276-017-1901-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative anatomy of the growing quadratus lumborum in the human foetus

Abstract: PurposesThe purpose of the study was to quantitatively evaluate the size of the quadratus lumborum and to precisely display its growth dynamics in the human foetus.Materials and methodsUsing anatomical dissection, digital-image analysis (NIS Elements AR 3.0) and statistical analysis (Student’s t test, regression analysis), the length, width, surface area, and cross-sectional area of the quadratus lumborum were measured, and the width-to-length ratio was calculated in 58 human foetuses of both sexes (26♂, 32♀) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…In accordance with the previous study results on morphometric properties of different muscle groups [2,4,13,14,17], this study revealed a rational increase in numerical values of TFL surface area, width and lengths from 18 th to 30 th week and showed no statistically significant difference between sides and sexes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In accordance with the previous study results on morphometric properties of different muscle groups [2,4,13,14,17], this study revealed a rational increase in numerical values of TFL surface area, width and lengths from 18 th to 30 th week and showed no statistically significant difference between sides and sexes.…”
Section: Discussionsupporting
confidence: 92%
“…Although literature reported a number of differences in many muscle growth dynamics between fetuses [2,4,13,14,17,25], no quantitative studies on TFL were…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The muscle acts as a lumbar spine extensor, a lumbar stabilizer, and is involved in lateral tilting. The innervation occurs through the ilioinguinal nerve, the iliohypogatric nerve, and twelfth thoracic intercostal nerve [20].…”
Section: Discussionmentioning
confidence: 99%
“…A study to quantitatively evaluate the QL in fetuses and its growth dynamics concluded a logarithmic increase in the length, width and cross-sectional area proportionate to age and can explain differences in paediatric musculoskeletal ultrasonography. [ 7 ] We suggest that in children a “dragonfly sign” may be more appropriate than the “Shamrock sign.”…”
mentioning
confidence: 99%